Türk Edebiyatında Hakikat Arayışları Ve Beşir Fuat - (:unkn) unknown (Selçuk Üniversitesi Türkiyat Araştırmaları Dergisi, 2017)
Literature is the science of beauty that blossoms into the inner human world. There are those who say truth cannot be sought in this science, as well as those who pursue the absolute truth. Should truth be sought in literature today as in the past? Or shouldn't it? The question seems to be an unresolved problem. In fact, it is known that every literary work has a fictional side to it. Consequently, more than a few artists believe that truth in literary works is an adorned truth.The concept of truth in Turkish literature that developed especially during what we call the Tanzimat (reformation) period (in Ottoman history) under western influence comprises a remarkable feature. Because people change and literature that has it as a subject needs to keep pace with this change. The currents of truth, realism and, a step further, naturalism, which artists including Şinasi, Namık Kemal and Ahmet Midhat particularly dwell upon, begin to keep the agenda busy. In the period we call the intermediate generation, we come across Beşir Fuat and artists who followed his footsteps. The method used in this article is one of criticism directed to the artist. To understand the artist one needs to look at his work and evaluate him accordingly. This principle carries importance in the method in question.

Edebiyat, insanın iç dünyasına açılan güzelliklerin ilmidir. Bu ilimde hakikat aranmaz diyenler kadar mutlak bir hakikat peşinde koşanlar da mevcuttur. Geçmişte olduğu gibi günümüzde de edebiyatta hakikat aranmalı mı? Yoksa aranmamalı mı? Sorunu çözümlenmemiş bir problem gibidir. Gerçekte her edebî eserin fiktif (kurgusal) bir tarafı olduğu bilinir. Bu nedenle edebî eserlerdeki hakikatin süslenmiş bir hakikat olduğunu düşünen sanatkârlar az değildir. Türk edebiyatında özellikle Tanzimat dönemi olarak adlandırdığımız batı tesirinde gelişen Türk edebiyatının hakikat anlayışı dikkat çekici bir özellik taşır. Çünkü insan değişmektedir ve onu konu olarak alan edebiyat da bu değişime ayak uydurmak zorundadır. Şinasi, Namık Kemal, Ahmet Midhat gibi sanatkârların üzerinde ayrıca durduğu hakikat, realizm ve onun bir adım ilerisi olan natüralizm akımlarıyla da gündemi meşgul etmeye başlar. Ara nesil olarak adlandırdığımız dönemde ise Beşir Fuat’ın ve onun yolunda giden sanatkârların izlerine rastlarız. Bu makalede yararlanılan metot sanatkâra dönük eleştiri metodudur. Sanatkârı anlamak için onun eserine bakmak ve sanatkâr hakkındaki değerlendirmeyi buna göre yapmak prensibi bu metotta önem taşımaktadır.
Keywords: Edebiyat; Türk Edebiyatı; Hakikat; Beşir Fuat; Literature; Turkish Literature; Truth